PERAN PEKERJA SOSIAL DALAM MENINGKATKAN DISIPLIN ANAK DI UNIT PELAKSANA TEKNIS (UPT) PANTI SOSIAL PENGASUH ANAK DINAS SOSIAL PROVINSI RIAU - Misdawati Misdawati; Titi Maemunaty; Desti irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Social workers have an important role in solving problems that are being faced by the community. therefore, the community needs the role of social workers as facilitators, social workers as mediators, social workers as defenders and social workers as protectors. This study aims to determine the Role of Social Workers in Improving Child Discipline in the Technical Implementation Unit (UPT) of the SocialCare Institution for Child Care of the Social Service of Riau Province. This study used descriptive qualitative method. The informants of this study consisted of 2 core informants, 1 control informant and 1 observer informant in the social care unit of the official child care unit of Riau province. Data collection techniques used are observation, interview and documentation. And data analysis techniques used are datareduction, data display, and examination of conclusions and verification. As well as data validity techniques by using the krebilita test, transferability testing, dependability testing and confirmation testing. The results of this study were obtained based on indicators, sub-indicators, dimensions of the Role of Social Workers in Improving Child Discipline. Based on the data, the researcher made interview guidelines for 54 items divided into 4 indicators developed into 12 sub-indicators and 13 dimensions, namely: 1Role of Social Workers As Facilitators named social workers facilitating all children's needs, and facilitating children living in the Institution's Technical Implementation Unit Social Child Care. 2 The Role of Social Workers as Mediators where social workers apply the rules to children and provide penalties to children who violate regulations in the Technical Unit of the Child Care Institution. 3 The Role of Social Workers As Defenders where social workers must defend troubled children in the Home. 4 Roles ofSocial Workers as Protectors. Social workers must protect children from environmental problems that children can be affected from outside the Social Institution Childcare.Keywords: The role of social workers and discipline